Postoperative Outcome of Short Segment Percutaneous Screw Fixation Compare with Long Segment Fixation in Thoracolumbar Fracture - Choovongkomol, MD, Kongtush; Piyapromdee, MD, Urawit; Tanaviriyachai, MD, Terdpong; Jongkittanakul, MD, Sarut; Sudprasert, MD, Weera (Journal of Southeast Asian Orthopaedics, 2022)
Objectives: To evaluate the postoperative outcome of percutaneous pedicle screw fixation (PPSF) using the proposed technique in the treatment of thoracolumbar spine fracture compared to an open long segment pedicle screw fixation technique (OPSF). Materials and Methods: A retrospective review of 49 cases of unstable thoracolumbar spine fracture patients (Burst fracture 44 cases and flexion-distraction 5 cases) without neuro deficit that treated at Maharat Nakhon Ratchasima hospital from January 2015 - December 2017. Demographics data, postoperative visual analog scale, intraoperative blood loss and length of stay were collected from medical records. Postoperative radiographic parameters were collected from the CT scan. Results: The mean kyphosis reduction was 11.2±4.6 degrees in the PPSF group and 11.5±4.8 degrees in the OPSF group. Mean canal diameter increase was 17.81±16.46 and 18.83±15.36 mm2 respectively. Mean VAS reduction was 4.55±1.87 and 4.63±2.16 respectively. There was no significant difference between the two groups in these three parameters (all P-values > .05). There was a statistically significant difference in intraoperative blood loss which was 56.36±36.64 ml in PPSF and 124.38±59.89 ml in OPSF (P < .05). Postoperative length of stay was no significantly difference between the both groups (PPSF 5.7±2.2 and OPSF5.8±2.1 respectively, P = .86). Conclusions: In terms of postoperative outcome, there were lack of evidence to detect the difference between PPSF and OPSF in postoperative radiologic outcomes, VAS reduction, postoperative length of stay and complications, but PPSF could reduce intraoperative blood loss.